Future as Past in Central Asian Gāndhārī: A Note on the Relationship between Aṣṭādhyāyī 3.2.112–114 and the Usage of the Future Tense to Denote Past Actions in Niya Prakrit - Giudice, Alessandro (Indo-Iranian journal, 2024)
This paper explores the potential relationship between Aṣṭādhyāyī 3.2.112–114 and the usage of the future tense to denote past actions in Niya Prakrit. According to the interpretation by vyākaraṇa commentators, rule A 3.2.112 teaches that the l-substitutes of lṚṬ (= sigmatic future) occur after a verbal base to denote a past action excluding the present day, provided that there is a co-occurring word conveying the sense of ‘recollection’; the other two rules (A 3.2.113–114) constitute the exceptions to the latter. Specifically addressing A 3.2.112, Thomas Burrow argued that, in six Niya Prakrit occurrences (CKD 182, 309, 376, 435, 621, 634), there is “exactly what is laid down in Pāṇini 3 2 112”. This paper endeavours to demonstrate that such alignment is not entirely accurate, at least according to the traditional interpretation of the rules at stake.